2016
DOI: 10.1016/j.bbalip.2015.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Altered myocardial metabolic adaptation to increased fatty acid availability in cardiomyocyte-specific CLOCK mutant mice

Abstract: A mismatch between fatty acid availability and utilization leads to cellular/organ dysfunction during cardiometabolic disease states (e.g., obesity, diabetes mellitus). This can precipitate cardiac dysfunction. The heart adapts to increased fatty acid availability at transcriptional, translational, post-translational and metabolic levels, thereby attenuating cardiomyopathy development. We have previously reported that the cardiomyocyte circadian clock regulates transcriptional responsiveness of the heart to ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 57 publications
2
20
0
Order By: Relevance
“…Conversely, inhibition of mTOR via TSC2 results in ablation of the peripheral circadian clock. In fact, mTOR appears to regulate BMAL1 via S6K1 mediated phosphorylation, (118) and control the central circadian clock via regulating the activity of the translational repressor, eukaryotic translational initiation factor 4E binding protein 1 (4E-BP1) (32) Intriguingly, restricting food intake to the active period (for 8 hours, at night time) in mice simultaneously restored circadian variations in TOR activity and prevented the dampening of circadian gene oscillations in mice fed high fat diet, with complete prevention of adverse metabolic consequences (85), and these findings recapitulate independent observations by other groups in murine models with varying dietary composition and timing of feeding (158, 221). Indeed, time-restricted feeding activated circadian cycling of autophagic flux in various tissues (128) and the associated metabolic effects were critically dependent on autophagy.…”
Section: Interplay Of Lysosome Function With the Metabolic Circadian supporting
confidence: 65%
“…Conversely, inhibition of mTOR via TSC2 results in ablation of the peripheral circadian clock. In fact, mTOR appears to regulate BMAL1 via S6K1 mediated phosphorylation, (118) and control the central circadian clock via regulating the activity of the translational repressor, eukaryotic translational initiation factor 4E binding protein 1 (4E-BP1) (32) Intriguingly, restricting food intake to the active period (for 8 hours, at night time) in mice simultaneously restored circadian variations in TOR activity and prevented the dampening of circadian gene oscillations in mice fed high fat diet, with complete prevention of adverse metabolic consequences (85), and these findings recapitulate independent observations by other groups in murine models with varying dietary composition and timing of feeding (158, 221). Indeed, time-restricted feeding activated circadian cycling of autophagic flux in various tissues (128) and the associated metabolic effects were critically dependent on autophagy.…”
Section: Interplay Of Lysosome Function With the Metabolic Circadian supporting
confidence: 65%
“…In mice, consumption of a high-fat meal at the end of the active period was associated with increased adiposity, decreased glucose tolerance, hyperinsulinemia, and decreased cardiac function (relative to mice fed the same high-fat meal during the beginning of the active period). 123 , 160 Interestingly, when placed on a high-fat diet in an ad libitum fashion, mice consume an abnormally high proportion of calories during the sleep phase, associated with phase and amplitude effects on peripheral circadian clock gene oscillations, as well as increased adiposity and depressed glucose and insulin tolerance. 62 However, limiting consumption of a high diet only to the active period resulted in improvements in these cardiometabolic parameters (relative to ad libitum high-fat feeding), and increased the amplitude of circadian clock gene expression in multiple metabolically relevant peripheral tissues (eg, liver).…”
Section: Physiologic Roles and Pathologic Consequencesmentioning
confidence: 99%
“…NAMPT expression oscillates in a circadian fashion in the heart (Um et al, 2011;Young et al, 2014;Peliciari-Garcia et al, 2016;Li et al, 2020). Previous studies have shown that Nampt gene expression is under the regulation of core clock machineries, circadian locomoter output cycles protein kaput (CLOCK) and brain and muscle Arnt-like protein 1 (BMAL1), as well as SIRT1, which leads to rhythmic cellular NAD + levels (Nakahata et al, 2009;Ramsey et al, 2009;Wijnen, 2009).…”
Section: Nad + Metabolism In the Heart Nad + Biosynthesismentioning
confidence: 99%